Effects of increasing wheat middlings and net energy formulation on nursery pig growth performance - De Jong, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 210 pigs (PIC 327 × 1050, initially 15.15 lb) were used in a 29-d trial to evaluate the effects of dietary wheat middlings and NE formulation on nursery pig growth performance. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. The 5 corn-soybean meal–based diets were: (1) corn-soybean meal (positive control), (2) 10% added midds, (3) 20% added midds, (4) Treatment 2 with 1.4% added soybean oil, and (5) Treatment 3 with 2.8% added soybean oil. Treatments 4 and 5 were balanced on an NE basis equal to that of the positive control. Feed ingredients were assigned NE values for the growing pig by INRA (20042). Treatment diets were fed in a 2-phase feeding program from d 0 to 12 and 12 to 29. From d 0 to 12, a midds × fat interaction was observed (P < 0.01) for ADFI. This was the result of pigs fed increasing midds having increased feed intake with no added fat but decreased intake when increasing fat was combined with increasing midds. From d 12 to 29, no midds × fat interactions were observed. For the main effects of midds (regardless of NE), there was a tendency for decreased (P < 0.09) ADG and poorer (P < 0.001) F/G. Feed efficiency was similar among pigs fed either 0 or 10% wheat midds, but decreased (quadratic, P < 0.03) when midds increased to 20% of the diet; however, balancing on a NE basis tended to increase (P < 0.09) ADG compared with not balancing for NE when midds were added.
Keywords: Swine; ME; NE; Nursery pig; Wheat middlings